Pengembangan Modul Pembelajaran Penataan Sanggul Modern Upstyle Untuk Siswa Pada Fase F Kecantikan Dan SPA Di SMK Negeri 27 Jakarta - Naflah Lutfi Nabillah; Nurul Hidayah; Aniesa Puspa Arum (Journal on Education, 2024)
The research was motivated by student learning outcomes that scored below the Minimum Completion Criteria KKM on the results of the theory understanding test. Answers were also obtained from the results of questions and answers to teachers of related subjects that the lack of student learning resources that can be accessed independently has caused a decline in student learning outcomes and less than optimal learning achievement. So that research is carried out to develop learning media that can be practically used by students as a learning media independently and can be utilized by teachers as teaching materials. The method used in this research is research and development with the ADDIE model approach which includes five stages, namely, Analyze, Design, Development, Implementation, and Evaluation. At the Implementation and Evaluation stages, instruments were distributed for product validation tests to two lecturers of material experts and media experts, one to one trials and small group tests to students at SMKN 27 Jakarta. The results obtained in the stage I material expert test = 58,8% and stage II 90%, in the stage I media expert test = 52% and stage II =86,6 %, in the one to one practical test the results were obtained 93,5%, and the small group practical test stage 94,4%. Based on the research that has been done, it is concluded that the Modern Up Style Bun Styling Learning Module can be used and applied for learning with the results that are feasible and practical to use.